2016
DOI: 10.1016/j.clnu.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of micronutrient deficiencies pre- and post-antiretroviral therapy (ART) among a diverse multicountry cohort of HIV-infected adults

Abstract: Background and Aims HIV-infected adults have increased risk of several individual micronutrient deficiencies. However, the prevalence and risk factors of concurrent and multiple micronutrient deficiencies and whether micronutrient concentrations change after antiretroviral therapy (ART) initiation have not been well described. The objective of this study was to determine the prevalence and risk factors of individual, concurrent and multiple micronutrient deficiencies among ART-naïve HIV-infected adults from ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
(41 reference statements)
1
30
2
3
Order By: Relevance
“…Unlike previous reports (eg, Shivakoti and colleagues, van den Bout‐van den Beukel and colleagues, Kwan and colleagues), there was no indication that either HIV infection or ART exposure was associated with compromised vitamin D status in these South African women. The mean 25(OH)D concentration in all three groups exceeded 50 nmol/L at both baseline and 12 months with no decrease over time in Ppres or Plow.…”
Section: Discussioncontrasting
confidence: 91%
“…Unlike previous reports (eg, Shivakoti and colleagues, van den Bout‐van den Beukel and colleagues, Kwan and colleagues), there was no indication that either HIV infection or ART exposure was associated with compromised vitamin D status in these South African women. The mean 25(OH)D concentration in all three groups exceeded 50 nmol/L at both baseline and 12 months with no decrease over time in Ppres or Plow.…”
Section: Discussioncontrasting
confidence: 91%
“…Using established deficiency cutoffs, 7% of cases and 3% of non-cases were deficient in vitamin A (<0.7 µmol/L), 31% and 37% in vitamin B6 (<19 nmol/L), 6% and 9% in vitamin B12 (<148 pmol/L), 22% and 14% in vitamin D (<20 ng/mL), 2% and 0% in α-tocopherol (vitamin E isoform) [<9.3 µmol/L], and 76% and 51% in selenium (<85 mg/L). Baseline micronutrient deficiency prevalence in the sub-cohort was previously described 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal vitamin D deficiency was significantly associated with disease or HIV-1 replication in three studies from the Western Cape [38,64,65], with vitamin D deficiency more severe in patients co-infected with HIV-1 and Mycobacterium tuberculosis [64]. Three multinational cohort studies which included participants from Gauteng and/or KwaZulu-Natal also found vitamin D deficiency in approximately 40%–50% of HIV-1-infected patients, but there was no control comparison group so that disease association could not be assessed [67,68,69]. Participants from the PEARLS (Prospective Evaluation of Antiretrovirals in Resource Limited Settings) trial were used in two of these studies.…”
Section: Association Of Vitamin D Status With Diseases In South Afmentioning
confidence: 99%
“…At 24 weeks after initiation of antiretroviral therapy (ART), patients receiving efavirenz-containing regimes had significantly decreased serum 25(OH)D concentration, with the greatest decrease occurring in those with higher baseline 25(OH)D levels. Notably ART did not improve micronutrient deficiency in HIV-1-infected persons [67,68]. …”
Section: Association Of Vitamin D Status With Diseases In South Afmentioning
confidence: 99%